Electric light commercial vehicles for a cleaner urban goods distribution. Are they cost competitive?. (March 2021) - Scorrano, Mariangela; Danielis, Romeo; Giansoldati, Marco
Abstract: The paper investigates the cost competitiveness of electric light commercial vehicles (eLCVs) with respect to their petrol and diesel counterparts. We develop a detailed total cost of ownership (TCO) model incorporating all relevant costs with special attention to account for variations in engine efficiency between urban and sub-urban trips and by seasons of the year. The model generates two metrics: the threshold purchase price and the threshold annual distance travelled, which are used to compare among propulsion systems and to perform policy scenarios. The model is applied to a large selection of LCVs models available in Europe as of June 2019. We find that eLCVs have on average a higher TCO/km than their conventional counterparts. Yet, the existing offer of eLCVs is differentiated and some eLCV models are cost competitive. We find that four eLCV models belonging to the city and panel segments are convenient relative to their diesel counterparts for daily distances travelled lower than 93 km. Nonetheless, with financial and regulatory incentives, 100% urban driving, and 100% home/depot charging, most of the existing city and panel eLCV models are cost competitive with respect to both their diesel and petrol counterparts. Highlights: We study the cost competitiveness of eLCV with respect to petrol and diesel ones. We classify LCVs into three groups: city, panel and box ones. We compute eLCV threshold-purchase price and -annual distance travelled. We evaluate the impact of urban driving, subsidies and access fees. eLCVs are convenient when used in urban areas and with policy incentives.